ChemInform Abstract: New Approach to Synthesis of 4‐Arylcoumarin Derivatives. Issue 9 (February 2016) - Bardasov, Ivan N.; Alekseeva, Anastasiya U.; Ershov, Oleg V.; Surazhskaya, Marina D.; Churakov, Andrei V.; Grishanov, Dmitry A.
Abstract: A novel and operationally simple synthesis of 4‐arylchromone‐3‐carbonitriles is rendered possible by oxidation and hydrolysis of 2‐amino‐4‐aryl‐4H‐chromene‐3‐carbonitriles using I2 O5 as the oxidant.